Promoting Social Justice Through Appreciative Community Service. Issue 143 (17th September 2013) - Mather, Peter C.; Konkle, Erin
Abstract: Social justice and community service have strong traditions in higher education. In this chapter, the authors describe ways in which positive psychology and appreciative inquiry inform the pursuit of social justice through community service activities.